Magnetic Fe₃O₄ nanoparticle/ZIF-8 composites for contaminant removal from water and enhanced flame retardancy of flexible polyurethane foams - Xu, Zhoumei (2022)
In order to separate heavy-metal ions from contaminated wastewater and further realize the reutilization of waste adsorbent, magnetic composites with flowerlike structure were successfully synthesized. After the absorption of Cu2+ions, hybrids can be used as effective coatings to enhance the fire safety of flexible polyurethane foam (FPUF) through a dip-coating method. As-fabricated metal-organic framework (MOF)-based composites exhibited a core-shell and flowerlike structure with high thermal stability. The maximum adsorption capacity for Cu2+could reach 292.13 mg·g-1, calculated from the Langmuir isotherm model. In order to reutilize the adsorbed Cu2+ions, the CuO-loaded MOF-derived Fe3O4@ZnO@CuO (MO) was obtained with a simple heat treatment. The effectivity of MO as a fire-safety coating for inhibiting the release of heat and toxic gases of FPUF was satisfactory. The application of this MOF-based composite will provide useful insights into the design of bifunctional materials for efficient wastewater remediation and fire-safety coatings.